Multiple Unit Auctions and Short Squeezes - Kjell G. Nyborg; Ilya A. Strebulaev (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper develops a theory of multiple unit auctions with short squeezes in the post- auction market. This is especially relevant for financial and commodity markets where players may enter the auction with established forward positions. We study how a potential short squeeze impacts on bidders' strategies and auction performance. Conversely, we also study how the design of the auction affects the incidence of short squeezes. In particular, we model both uniform price and discriminatory price auctions in a true multiple unit setting, where bidders can submit multiple bids for multiple units. Our model is cast in what appears to be a common value framework. However, we show that the possibility of a short squeeze introduces different valuations of the to-be-auctioned asset between short and long bidders.
Keywords: D44; G12; G20; D62; 330; Multiple unit auction; uniform auction; discriminatory auction; treasury auction; repo auction; short squeeze; market manipulation; market power; Auktionstheorie; Theorie